Technological Innovation Adoption In Malaysia High Tech Industry From The Perspective Of Intellectual Capital And Knowledge Management Infrastructure: The Knowledge Creation Capability As A Mediator - Leong, Shi Qi (2012)
The aims of this study were to: (a) examine the direct effect of Intellectual Capital and Technological Innovation; (b) Understand the direct impact of Knowledge Management Infrastructure and Technological Innovation; and (c) investigate whether knowledge creation capability acts as a mediator role in the above relationship. Technological innovation was conceptualized into two dimensions of radical technological innovation and incremental technological innovation. The intellectual capital comprise of three dimensions of human capital, social capital and structural capital. The knowledge management infrastructure was operationalized into two dimensions of technological knowledge management infrastructure and structural knowledge management infrastructure. The mediator of knowledge creation capability was illustrated as single dimension. Seven broadly hypotheses were postulated and tested using a sample of 110 Malaysia high technology organizations representing 34.60 percent response rate in this study.